In vitro glucose uptake by isolated rat hemi-diaphragm study of Aegle marmelos Correa root - M. Rupeshkumar; T. Balasubramanian; T. Tamizmani; Subban Ravi; C.T. Sadashiva; Indira Balachandran (Bangladesh Pharmacological Society, 2009)
The methanol extract of the root of Aegle marmelos, a medicinal plant, was fractionated into eight fractions using column chromatography. The anti-diabetic activity of all the fractions was studied using the glucose uptake by isolated rat hemi-diaphragm in vitro model. Using the bioassay-guided fractionation, two compounds 1 and 2 were isolated by column chromatography and identified as 6-methyl-4-chromanone and skimmianine respectively by NMR and mass spectral methods.